(untitled) (Experimental biology, 2015)
The callus tissues of Gypsophyla rupestris Kupr. were obtained for the first time from ascetic sprouts in Murashige and Skoog (МS) medium with phytohormones BAP- 1 mg/l : IAA- 2 mg/l. For minimizing growth of Gypsophyla rupestris Kupr. callus tissues was used 50 % and 100 % MS medium with retardants, together with low positive temperatures (+5оС). Optimum concentration of retardants for delay of growthregulating activity and viability renewal, after transfer to normal conditions of callus tissues are 5%, 10 % sucrose and combination of 5 % sucrose and 2 % mannite.